THE SAUDI ARABIAN MONETARY AGENCY AND ITS ROLE IN FINANCIAL BALANCE IN THE KINGDOM OF SAUDI ARABIA (World Economics and Finance Bulletin, 2025)
Saudi Arabia's economy is among the fastest expanding in the area of the Middle East as well as North Africa. The Saudi economy continues to thrive despite the harsh global conditions caused by the worldwide financial crisis including the resultant drop in oil prices in 2009, despite the consequences of this crisis. The combination of financial and monetary policies in the Kingdom and the continuation of structural and organizational changes enabled the economy of Saudi Arabia to continue its growth in 2009, achieving acceptable economic growth rates with a decrease in the general price level .